(untitled) (London Journal of Research In Humanities and Social Sciences, 2026)
Virtual Education was born in 2002 from a joint project between the Center for Improvement, Experimentation and Pedagogical Research CPEIP and the Links Center for Education and Technology. CPEIP has developed a line of distance teacher training through the Internet, running several courses since 2002, and Links during the last for 15 years, it has dedicated its efforts to providing teachers and students with access to educational opportunities associated with new information and communication technologies. Both institutions decided to join forces and develop a joint project that integrates the CPEIP distance teacher training line, until now aimed at updating the curriculum, different strategies to support the appropriation of ICTs and their curricular integration.